2018
DOI: 10.1016/j.colsurfb.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Silica and carbon decorated silica nanosheet impact on primary human immune cells

Abstract: Silica nanosheets (SiO NS) are considered to be a promising material in clinical practice for diagnosis and therapy applications. However, an appropriate surface functionalization is essential to guarantee high biocompatibility and molecule loading ability. Although SiO NS are chemically stable, its effects on immune systems are still being explored. In this work, we successfully synthesized a novel 2D multilayer SiO NS and SiO NS coated with carbon (C/SiO NS), and evaluated their impact on human Peripheral Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…These peaks are in good agreement with previously reported XPS data for Silver oxide [46,47]. The peaks at 570.9 eV and 601.1 eV, corresponding to Ag 3p 3/2 and Ag 3p 1/2 related to the Ag 2 O films [48]. The O 1 s peak at a binding energy of 530.1 eV with full-width at half maximum (FWHM) of 1.9 eV in Fig.…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 91%
See 1 more Smart Citation
“…These peaks are in good agreement with previously reported XPS data for Silver oxide [46,47]. The peaks at 570.9 eV and 601.1 eV, corresponding to Ag 3p 3/2 and Ag 3p 1/2 related to the Ag 2 O films [48]. The O 1 s peak at a binding energy of 530.1 eV with full-width at half maximum (FWHM) of 1.9 eV in Fig.…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 91%
“…In contrast, O 1s shifted to 530.7 eV [51], accompanied by the formation of the new O 1s peak at 527.7 attributed to the formation of mixed-phase of Ag and Ag 2 O and in agreement with observed Ag x O phase in the literature [52] as seen in the XRD. These core level binding energies in the films formed at 120 and 900 s oxidation time were in a good agreement with the energies Ag 2 O, as reported by Abe et al [47,48] in plasma treated silver nanoparticles. This shift is consistent with previously published reports where the Ag 3d 5/2 core level binding energies in Ag and Ag 2 O and O 1 s compared with the pure metallic silver [47,52].…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 90%
“…To this end, we treated human peripheral blood mononuclear cells (PBMCs) with increasing concentrations (25, 50, and 100 μg mL −1 ) of V 4 C 3 or Ti 3 C 2 for 24 h, selecting this incubation time based on previous studies with other nanomaterials on immune cells. [14,[66][67][68][69][70][71][72][73][74][75][76][77] We used EtOH as a positive control. Subsequently, we stained cells with Fixable Viability Staining 780 and analyzed the effect of material exposure by flow cytometry, observing no reduction of PBMC viability (Figure S1B, Supporting Information).…”
Section: Hemocompatibility and Immunocompatibility Of V 4 C 3 Mxenementioning
confidence: 99%
“…Toll-like 9 receptors recognized CpG and therefore, has been used for targeted delivery. Similarly, silica nanosheets alone and coated with carbon were evaluated for biocompatibility in peripheral blood mononuclear cells (PBMCs) (Al Soubaihi et al, 2018). The results revealed that carbon coating enhanced biocompatibility and less hemoglobin release, cytotoxicity, and no direct acute immune response.…”
Section: Influence Of Surface Properties Of Nanomaterialsmentioning
confidence: 99%